Gene Expression Profiles Reveal Extracellular Matrix and Inflammatory Signaling in Radiation-Induced Premature Differentiation of Human Fibroblast in vitro - Herskind, Carsten; Sticht, Carsten; Sami, Ahmad; Giordano, Frank A.; Wenz, Frederik (Frontiers in Cell and Developmental Biology, 2021)
Purpose: Fibroblasts are considered to play a major role in the development of fibrotic reaction after radiotherapy and premature radiation-induced differentiation has been proposed as a cellular basis. The purpose was to relate gene expression profiles to radiation-induced phenotypic changes of human skin fibroblasts relevant for radiogenic fibrosis. Materials and Methods: Exponentially growing or confluent human skin fibroblast strains were irradiated in vitro with 1-3 fractions of 4 Gy X-rays. The differentiated phenotype was detected by cytomorphological scoring and immunofluorescence microscopy. Microarray analysis was performed on Human Genome U133 plus2.0 microarrays (Affymetrix) with JMP Genomics software, and pathway analysis with Reactome R-package. The expression levels and kinetics of selected genes were validated with real-time PCR. Results: Irradiation of exponentially growing fibroblast with 1×4 Gy resulted in phenotypic differentiation over a 5-day period. This was accompanied by downregulation of cell cycle-related genes and upregulation of collagen and other extracellular matrix (ECM)-related genes. Pathway analysis confirmed inactivation of proliferation and upregulation of ECM- and glycosaminoglycan (GAG)-related pathways. Furthermore, pathways related to inflammatory reactions were upregulated, and potential induction and signaling mechanisms identified. Fractionated irradiation (3×4 Gy) of confluent cultures according to a previously published protocol for predicting the risk of fibrosis after radiotherapy showed similar downregulation but differences in upregulated genes and pathways. Conclusion: Gene expression profiles after irradiation of exponentially growing cells were related to radiation-induced differentiation and inflammatory reactions, and potential signaling mechanisms. Upregulated pathways by different irradiation protocols may reflect different aspects of the fibrogenic process thus providing a model system for further hypothesis-based studies of radiation-induced fibrogenesis.